History education in post-conflict societies - Sirkka Ahonen (Historical Encounters: A Journal of Historical Consciousness, Historical Cultures, and History Education, 2014)
This article studies the reconciliatory potential of history education in post-conflict societies. History education today is understood through post-colonial, multiperspectival studies, which in a post-conflict society contribute to reconciliation by fostering critical thinking, being inclusive in regard to different social groups, and recognising the local, vernacular history culture. The article compares three cases of post-conflict history education, derived from Finland, Bosnia-Herzegovina and South Africa. It concludes by considering the nature of feasible teaching processes and the role of different educational actors.